Microglia promote colonization of brain tissue by breast cancer cells in a Wnt-dependent way - Pukrop, Tobias; Heermann, Stephan; Hoffmann, Anja (Glia, 2010)
Although there is increasing evidence that blood-derived macrophages support tumor progression, it is still unclear whether specialized resident macrophages, such as brain microglia, also play a prominent role in metastasis formation. Here, we show that microglia enhance invasion and colonization of brain tissue by breast cancer cells, serving both as active transporters and guiding rails. This is antagonized by inactivation of microglia as well as by the Wnt inhibitor Dickkopf-2. Proinvasive microglia demonstrate altered morphology, but neither upregulation of M2-like cytokines nor differential gene expression. Bacterial lipopolysacharide shifts tumor-educated microglia into a classical M1 phenotype, reduces their proinvasive function, and unmasks inflammatory and Wnt signaling as the most strongly regulated pathways. Histological findings in human brain metastases underline the significance of these results. In conclusion, microglia are critical for the successful colonization of the brain by epithelial cancer cells, suggesting inhibition of proinvasive microglia as a promising antimetastatic strategy. © 2010 Wiley-Liss, Inc.